Effect of enzymatic treatment on CCN-51 clone cacao pulping: physicochemical characteristics, polyphenols content and antioxidant activity (Research, Society and Development, 2020)
The objective of the present work was to evaluate the influence of enzymatic maceration with pectinases on CCN-51 clone cocoa pulp, by means of yield, physicochemical aspects, polyphenol content, and antioxidant activity of diluted cocoa pulp (PCD). Three treatments were conducted. In the T1 treatment, the pulp was added water in the proportion of 1: 3 (m / v) and the Pectinex ULTRA SP-L enzyme complex, the mixture being kept at 45 °C for 15 minutes under agitation; in T2 there was no enzymes addition and in T3 the pulp was extracted manually. The PCD were subjected to physicochemical analyzes of pH, acidity, color, moisture, ash, lipids, proteins and reducing sugars; in addition to the content of total extractable polyphenols and antioxidant activity by the radicals ABTS•+ and DPPH methods. T3 showed the highest yield (32.04%), however the presence of the enzyme increased the value by more than 100% (T1 = 22.45%) when compared to the control (T2 = 11.18%). T1 showed the lowest pH (3.39) and the highest acidity (0.10%). The enzymatic treatment did not change the color parameters of the PCD when compared to the manual process. The extraction methods did not significantly influence the chemical composition of the PCD. The content of polyphenols was higher for T1 (7.47 mg / 100 g), which also showed the best antioxidant activity by the two methods evaluated. It can be concluded that the enzymatic treatment had a positive influence on the yield, on the extraction of polyphenols and on the antioxidant activity of the diluted cocoa pulp.